Culture Technique of Sunu Grouper (Plectropomus Leopardus) Broodstock in a concrete pond in Gondol, Bali Marine Research and Development Center - Gia Asasa Ghassani; Adriana Monica Sahidu (Universitas Airlangga, 2018)
(Plectropomus leopardus) or grouper coral trout is one kind of commodities that have high economic value. As marine fisheries commodities are much in demand for large-scale farmers or household level will require broodstock who have qualified to produce quality eggs and a good seed. qualified to produce quality eggs and a good seed. The purpose of research is to gain knowledge in maintenance activities of the broodstock grouper coral trout on a concrete tank by comparing theory and application in the field. Maintenance engineering of coral trout grouper broodstock includes the preparation of concrete tanks, broodstock selection, water quality management, feeding, spawning and harvesting of eggs, and disease. Research in Balai Besar Penelitian dan Pengembangan Budidaya Laut (BBPPBL) Gondol. Penyabangan Village, Subdistrict Gerokgak, Buleleng, Bali. On 18th January – 18th February 2016. Methods of work used in this research is descriptive data retrieval methods include primary data and secondary data. Data retrieval is done by means of active participation, observation, interviews and literature study. Results of Field Work Practice is the broodstock of grouper coral trout are maintained as much 217 with an average weight of 512.9 kg and an average length of 56.1 cm. Maintenance of broodstock grouper coral trout performed in container maintenance the round-shaped sized 100 m3 with a depth of 3 m with inlet and outlet Water management is performed by using a system is running water that flowing water as much as 300% -400%, the quality of sea water showing the value of 34.9 ppt salinity, DO 6.0 ppm, pH 8, and the temperature of 29 ˚C. Feed given in the form trash fish as much as 7-10 kg a day. Grouper coral trout spawning is done naturally by the male and female parent ratio of 1: 2, which produce eggs an average 2,252,292 items. During maintenance activities parasites invade have been found. Parasites invade the broodstock of grouper coral trout is Benedenia sp., Cryptocaryon sp., And viral infections Viral Nervous Necrosis (VNN)